Design Build a 2D Game “The Greatness of The Labyrint Road” Using RPG MakerMV - Errindha Brilliana Karuniansyah; Cindy Taurusta (Procedia of Engineering and Life Science, 2022)
A game or game is something that can be played with certain rules so that there are winners and losers. This study aims to create a 2D RPG genre game. With a maze theme and this game was created using the RPG MakerMVapplication. System development in games uses the MDLC (Multimedia Development Life Cycle) method. This gamehas been successfully developed and tested using blackbox testing and user questionnaires. The results obtained are researchers can test children's patience in finding a way in the maze